Thermo-enhanced photocatalytic oxidation of amines to imines over MIL-125-NH2@Ag@COF hybrids under visible light - Li, Xiangjun; Zhang, Kaiyue; Huang, Xiubing; Wu, Zhenyu; Zhao, Danfeng; Wang, Ge (Nanoscale, 2021)
Thermo-enhanced photocatalysis combines the advantages of thermocatalysis and photocatalysis and provides a very promising approach for the selective oxidation of organic compounds to value-added chemicals. In this work, the amino group in MIL-125-NH2 first reacts with formaldehyde to form the reducing group (–NH–CH2OH), which can in situ auto reduce the introduced Ag+ ions to Ag clusters/nanoparticles in the cavities. Then the formed MIL-125-NH–CH2OH@Ag was further coated with a covalent organic framework (COF) through imine bonds to form a series of MIL-125-NH–CH2OH@Ag@COF hybrids. Oxidative coupling of amines was selected to evaluate the photocatalytic performance of these materials under visible light at set temperatures (20–60 °C). With an optimized composition, MIL-125-NH–CH2OH@Ag-0.5@COF-2 not only improves the optical properties, but also exhibits the highest conversion (almost 100%) of benzylamine under visible light at 60 °C and good stability for at least three cycles. Free radical capture experiments and electron spin resonance detection demonstrated that holes (h+), hydroxyl (·OH) and superoxide radicals (O2·−) were the active species. The results prove that the MIL-125-NH–CH2OH@Ag@COF hybrid possessed higher photocatalytic performance than individual MIL-125-NH2, Ag and COF on account of the efficient separation and transfer of photoinduced electrons and holes. Moreover, the promotion of the reaction temperature on the photocatalytic oxidation of amines has been reported, revealing that the conversion of benzylamine over MIL-125-NH–CH2OH@Ag-0.5@COF-2 at 60 °C is nearly twice as high as that at 20 °C under visible light irradiation. Therefore, the thermo-enhanced photocatalytic oxidation performance of the MOF@Ag@COF hybrid demonstrates the great potential of thermal energy for further improving the photocatalytic selective oxidation performance.